Estimation of the Efficiency of Material Injection into the Reflex Discharge by Sputtering the Cathode Material - Kovtun, Yu.V.; Skibenko, E.I.; Skibenko, A.I.; Yuferov, V.B. (Ukrainian Journal of Physics, 2012)
The processes of injection of a sputtered-and-ionized working material into the pulsed reflex discharge plasma have been considered at the initial stage of dense gas-metal plasma formation. A calculation model has been proposed to estimate the parameters of the sputtering mechanism for the required working material to be injected into the discharge. The data obtained are in good accordance with experimental results.